'A Bunch of Riffs': Language, Post-Modernity, and the Politics of Inclusion in Improvised Music. Issue 5 (3rd September 2019) - Eisenberg, Wendy
Abstract : Jazz improvisation is as dependent on the use of pre-existing riffs as it is on extemporaneous creation. These riffs create, establish, and reference genres, and provide an extra-temporal aspect to the moment of performance. The re-appropriation of these musical fragments transforms their meaning and purpose in jazz convention. This paper looks toward the work of Anthony Braxton, Cecil Taylor, Sun Ra, Marilyn Crispell, and Charlie Parker in order to clarify how the cultural context of particular riffs influences which improvisational languages are deemed 'legitimate'. It also questions how such 'legitimacy' functions in a genre defined by constant evolution. Using writings from Frederic Jameson, Rosalind Krauss, LeRoi Jones, Donna Haraway, and Jürgen Habermas, I consider the riff as postmodernist tool, a repetitious device that speaks not to the dream of a common language, but the unity or crisis of differing voices.